On crossing of a level by processes defined by sums of a random number of terms - Gusak, D. V. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We study the joint distribution of boundary functionals related to the crossing of a positive (negative) level by a process consisting of a homogeneous Poisson process and a process defined by sums of a random number of continuously distributed terms.